An epidemiologic investigation of snowboarding injuries: Rates and risk factors. - Lipskie, Tammy L. (University of Ottawa (Canada), 2000)
This thesis study employed epidemiologic methods to investigate snowboarding injuries and, where appropriate, included alpine skiing injuries. There were two components: a descriptive component and an etiologic component. The injuries were described as proportions of the total number of respective sports injuries. Crude, specific and standardized injury rates were calculated. A variant of the case-control design was then used to identify potential risk factors for the more severe snowboarding injuries. This project built upon previous studies and contributes to the growing body of knowledge regarding snowboarding injuries. The large sample size provided statistical power often lacking in other studies. This project investigated 2,501 snowboarding injuries experienced at 71 ski centres across the province of Quebec during the 1996/97 ski season. The descriptions of snowboarding injuries in this project reinforce what has been published. However, the additional information provided by the participation data permits assessment of age and sex distributions in the injured sports enthusiasts. (Abstract shortened by UMI.)
Keywords: Health Sciences, Public Health.